(untitled) (Fiep Bulletin - online, 2024)
The number of elderly people has gradually increased in recent decades, and with this, the need for the creation of new alternatives to develop actions that seek to meet and improve the quality of life of this demand through physical exercise. Thus, the present study presents the project “Viver Bem É de Casa”, developed in the municipality of Encantado, located in the Northwest of Rio Grande do Sul. We sought to know whether the project brought benefits to its participants and which ones, through a quantitative and opinion research. Furthermore, we briefly discussed what aging is and the possibility of this process being healthier through the performance of physical activities even in situations where the Elderly Person is bedridden, in a wheelchair or has other difficulties, based on the conceptualization of aging. WHO and how these concepts appear in the Viver Bem É de Casa project. Keywords: Physical activity. Elderly. Living Well is from Home Project